2007
DOI: 10.1007/s10165-007-0582-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher maximal serum concentration of methotrexate predicts the incidence of adverse reactions in Japanese rheumatoid arthritis patients

Abstract: Weekly pulsed low-dose methotrexate (MTX) is a standard regimen for rheumatoid arthritis (RA). Severe adverse reactions to MTX, such as pneumonia and cytopenia, sometimes occur; however, it is difficult to predict the development of these adverse reactions. In this article, we examine the serum concentrations of orally administered MTX of 69 Japanese patients with RA in the clinical setting. The maximum serum concentration (C (max)) after the first dose of the weekly administration and the time at which C (max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Nonetheless, MTX-induced myelosuppression also develops in Japanese patients at a certain frequency independently of MTX dosage. In fact, Wyeth Corporation announced that MTX-related fatalities excluding those related to generics were 319 from 12 March 12 1999 to 31 December 2008 in Japan, and among them, the percentage of myelotoxicity was 36.7% (117 patients) [3]. As with other studies, the results of our study suggest that MTX may induce myelotoxicity more frequently than noted in the literature listed in references described later, which has supposedly underreported the prevalence of myelotoxicity [4].…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Nonetheless, MTX-induced myelosuppression also develops in Japanese patients at a certain frequency independently of MTX dosage. In fact, Wyeth Corporation announced that MTX-related fatalities excluding those related to generics were 319 from 12 March 12 1999 to 31 December 2008 in Japan, and among them, the percentage of myelotoxicity was 36.7% (117 patients) [3]. As with other studies, the results of our study suggest that MTX may induce myelotoxicity more frequently than noted in the literature listed in references described later, which has supposedly underreported the prevalence of myelotoxicity [4].…”
Section: Introductioncontrasting
confidence: 56%
“…It has been reported that patients with the maximum level of serum MTX concentration suffer ILD and liver dysfunction, the prevalence of the adverse events being higher in these patients than in patients with no adverse events [31]. The correlation may be observed between renal insufficiency and these events, although it is considered incidental for these reasons: (1) identified risk factors of MTX-induced ILD are hypoalbuminemia prior to DMARD administration, diabetes, and older age [32]; (2) our logistic regression analysis demonstrated that renal insufficiency did not contribute to these events.…”
Section: Discussionmentioning
confidence: 98%
“…There had been reported that some factors are probably correlated with ADRs in RA patients, such as a higher body mass index (BMI) (Verstappen et al, 2010), the maximum serum concentration -C after the first dose of the weekly MTX administration (Shoda et al, 2007), increasing age (McKendry and Dale, 1993), the IgG, IgA, and IgM, and lymphocyte count reductions and reduction ratios (Inokuma et al, 2000), genetic variation within ADORA2a (Hider et al, 2008). All these factors showed significantly association with MTX-related ADRs in different studies.…”
Section: Figmentioning
confidence: 99%
“…It is generally agreed that autoreactive antibodies may cause elimination of leukocytes and thus contribute to immune deficiency [4, 13]. Methotrexate and occasionally, prednisone, the popular drug for autoimmune diseases, are known to cause cytopenia [14–18]. On the other hand, lymphopenia has been shown to cause homeostatic proliferation (HP) of T cells [1922].…”
Section: Introductionmentioning
confidence: 99%
“…A well-established autoimmune disease in both adults and children is autoimmune hemolytic anemia, in which autoreactive antibodies are abnormally produced and mediate elimination of both erythrocytes and/or leukocytes [4, 13]. In addition, it is increasingly clear that drugs frequently used for autoimmune patients, such as methotrexate and occasionally prednisone, may have cytopenia as a major adverse event [14–18]. A largely overlooked issue is whether autoimmune diseases may cause defective hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%